Bekarang: Kearifan Lokal Masyarakat Pesisir Pulau Bintan - Rahma Syafitri (Hermeneutika : Jurnal Hermeneutika, 2022)
Sustainable fishing is one of the efforts to maintain fish resources. Bintan Island is one of the islands that has abundant fish resources. One of the phenomena of local wisdom of coastal communities on Bintan Island is bekarang. Bekarang is an activity to catch fish resources at low tide. The purpose of this study was to obtain detailed information about recent activities on Bintan Island. The data collection techniques used in this study were interviews and observation. Interviews were conducted by interviewing people who used to do later activities. In comparison, the observations were made by observing the activities of bekarang on the coast of Bintan Island, which aims to see firsthand how the actions of bekarang itself. The result of this paper is that now it is an activity to find fish resources on foot when the seawater is receding. The fish resources that the people of Bintan Island currently target are shellfish and snails, as well as other marine products that can be consumed. The advantages of bekarang are that it tends not to damage coastal and marine ecosystems, it is easy to do, bycatch can be avoided, catching is not carried out every day. The disadvantage of bekarang is that ordinary people who do not understand using bekarang techniques tend to damage the ecosystem. But if in a large number of members. Keywords: Bekarang, Local Wisdom, Bintan.